Банковские риски и научно-методические основы их формирования - Байрамова, Р. Ш.; Bayramova, R. (КНТУ, 2014)
У статті досліджені науково-методичні основи присутності ризиків у банківській діяльності. Аналізується природа та сутність економічного ризику. Автором запропонована класифікація ризиків у кредитно-грошовій системі. The article examines the scientific and methodological basis of the presence of risks in banks. Analyzes the nature and essence of economic risk. The author gives a classification of risks in the monetary system. The study revealed that to date there is no single understanding of the risk. We give a few different concepts of risk of economic doctrines. At risk in the banking practice we understand the danger (possibility) of the bank loss of their resources, revenue or work extra costs as a result of certain financial transactions etc.
Банківські ризики і науково-методичні основи їх формування
Risks in the operations of banks and their scientific and methodological basis
Keywords: банковский сектор; кредитно-денежная система; риск; кредитный риск; классификация рисков; банківський сектор; кредитно-грошова система; ризик; кредитний ризик; класифікація ризиків; banking; monetary and banking system; the risk; classification of credit risk